Violence at work - Chappell, Duncan; Di Martino, Vittorio (International Labour Office, 2006)
Provides a basis for understanding the nature of workplace violence and suggests ways of preventing it in the future. Focuses on those data, experiences and publications which best help to explain and interpret the roots of violence at work, and to promote proactive initiatives.
Keywords: Violence in the workplace.; Employee crimes.; Violence in the workplace -- Prevention.; Violence en milieu de travail.; Violence en milieu de travail -- Prévention.; Criminalité en milieu de travail.; BUSINESS & ECONOMICS -- Workplace Culture.; BUSINESS & ECONOMICS -- Human Resources & Personnel Management.; Violence.; Lieu de travail.; Conditions de travail.; Droit du travail.; Organisation internationale du travail.; Organisation mondiale de la santé.; UE/CE Union européenne.; Violence in the workplace -- Prevention; Employee crimes; Violence in the workplace; Arbeid.; Geweld.; workplace violence.; occupational safety.; developed countries.; developing countries.; legal aspect.; bullying at work.; sexual harassment.; cultural factor.; drug abuse.; alcoholism.; mental disease.; psychological aspect.; work environment.; employers liability.; role of ILO.; international organization.; good practices.; violence au travail.; sécurité du travail.; pays développés.; pays en développement.; aspect juridique.; persécution au travail.; harcèlement sexuel.; facteur culturel.; abus des drogues.; alcoolisme.; maladie mentale.; aspect psychologique.; milieu de travail.; responsabilité de l'employeur.; rôle de l'OIT.; organisation internationale.; bonnes pratiques.; violencia en el trabajo.; seguridad en el trabajo.; países desarrollados.; países en desarrollo.; aspecto jurídico.; acoso laboral.; acoso sexual.; factor cultural.; uso indebido de drogas.; alcoholismo.; enfermedad mental.; aspecto psicológico.; ambiente de trabajo.; responsabilidad del empleador.; papel de la OIT.; organización internacional.; buenas prácticas.; Guide.; ILO pub.; Pub OIT.; Guía.